Knowledge Relationship with Maternal Anxiety in Breastfeeding Babies during the Covid-19 Pandemic at UPTD Puskesmas Bawomataluo in 2021 - Alfirida Simanungkalit; Anastasia Luahambowo; Lisbet.E.F.Siregar; Dear Sari Br. Purba; Chrismis Novalinda Ginting (Britain International of Exact Sciences (BIoEx) Journal, 2022)
Breast milk is the main food source for babies who contain a variety of vitamins, proteins, and fats. However, with the increase in the Covid-19 pandemic, many mothers do not breastfeed their babies, because they are worried that their babies will contract the Covid-19 virus. This is due to the lack of information obtained by mothers, that the Covid-19 virus cannot be transmitted through breast milk. This study aims to find out the relationship of knowledge with maternal anxiety in breastfeeding in infants during the Covid-19 pandemic. This type of quantitative research with an analytical descriptive approach, conducted at UPTD Bawomataluo, November to December 2021. A population of 61 nursing mothers, a large determination of the total sampling sample. Univariate data analysis and bivariate analysis, Chi-Square test, a significant level of 0.05. The majority of respondents had less knowledge than 43 respondents (70.2%). The majority of respondents had a severe anxiety level of 31 respondents (50.8%). The results of bivariate analysis of knowledge relationship and anxiety level obtained value p-value = 0.000 < = 0.05. Concluded, it can be concluded that there is a meaningful relationship between the level of knowledge and anxiety levels of breastfeeding mothers in the Covid-19 pandemic.